Vietnam : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2006)
The Joint Staff Advisory Note (JSAN) describes the progress of Vietnam over the last two years. It expects that many of the shortfalls experienced in the implementation of the Comprehensive Poverty Reduction and Growth Strategy will be addressed by the new Socio-economic Development plan (SEDP) 2006-10, and describes both the developmental challenges that lie ahead for the coming plan period along with the consultative process that is underpinning the preparation of the SEDP.